Developing Artificial Moral Agents: Key Research Processes, Techniques, and Challenges - Ghazali , Fatemeh; BaniRostam, Touraj; Pedram, Mirmohsen (AI and Tech in Behavioral and Social Sciences, 2025)
The increasing influence of artificial intelligence (AI) on overall life aspects has led to numerous worries despite its advantages, providing a better quality of life for humans. Therefore, some mechanisms are required to enhance individuals’ trust in computer systems and prevent the adverse autonomous behaviors of intelligent agents. Consideration of the cognitive potentials of humans and use it in intelligent systems is an undeniable principle and shortcut. Therefore, morality and ethics in AI have received attention in theory and practice over recent decades. This study investigates the attempts to develop artificial moral agents based on an engineering viewpoint that focuses on technical aspects. The current challenges and gaps are expressed, and some recommendations are proposed for those interested in further studies in this field.